OIL SARDINE FISHERY IN THE MANGALORE ZONE DURING THE SEASONS 1963—64 AND 1967—68 - Prabhu, M S; Dhulkhed, M H (Indian Journal of Fisheries, 2011)
The oil sardine fishery in the Mangalore zone showed an upward trend from1963-64 to 1966-67 when the catches increased seven-fold from 52 to 386 tonnes, whichwas followed by a slight decline to 243 tonnes in 1967-68. Among the gears operated forthe oil sardine fishery, the highest catch-per-unit-efFort values were obtained for thecast net, chala bale and rampant. The best catches of oil sardine were obtained duringSeptember-December period when temperature and salinity values ranged 25.5 to 28.6''Cand 28.98 to 34.36 %, respectively. The length frequency studies indicate that the oilsardine attains a size of about 100-110 mm during the first year, 150-160 mm during thesecond year and 175-180 mm during the third year of its appearance. The fishery duringthe various years was supported by difierent year classes. One and two-year olds dominatedin 1963-64, 1966-67 and 1967-68 and one-year olds in 1964-65. In 1965-66,one-year olds formed the mainstay of the fishery, although the two-year olds also contributedfrom December onwards. O-year class was seen entering the fishery duringthe months of August and September in 1964-65, 1965-66 and 1966-67, as also in Octoberand again in January and February during 1967-68. Two or more broods have beenobserved to enter the fishery during certain years. Judged from the rate of growth andthe size attained by the smaller size groups composing the O-year class, the interval betweenthe entries of various broods has been observed to vary from one to three months.The estimated average rate of decrease diu'ing the five-year period worked out to 0.72,the instantaneous rate of mortality being 1.27.